EXAMINING THE FAITH-BASED US FOREIGN POLICY OF G.W. BUSH IN EXECUTING MIDDLE EASTERN AFFAIRS - Layada, Radia (PEOPLE: International Journal of Social Sciences, 2020)
The eager towards maintaining all initiatives linked to globalization and international power has permitted nations to interrupt the use of religion in framing its foreign policy agenda. Such use, though some countries consider as a part of the nation’s defense strategy, has characterized the new millennium by a massive disorder threatening international political stability. This geopolitical situation forces researchers to go further in questioning the intercourse between the faith-based foreign policy constructing process and the soft, hard, and smart powers used by nations. The present paper highlights the presence of religion in skeletoning the US foreign policy under the George W. Bush presidency and its effect on the US- Middle Eastern political relationships. With the implication of Bush’s faith, the paper identifies how the president’s foreign policy has been ultimately characterized by an evangelical presidential style and addressed domestically or internationally by extensive use of religious rhetoric.